Development of an Avian Influenza Virus H5N1 DNA Vaccine and the Use of MDP-1 Gene of Mycobacterium Bovis as Genetic Adjuvant - Jalilian, Babak (2008)
Avian influenza (AI) virus subtype H5N1 is a highly pathogenic virus that causes acute infection with high mortality in susceptible birds. Additionally, the virus can also cause lethal infection in human. Effective control of AI requires various strategies which comprises of vaccination, biosecurity, education, diagnostics and surveillance. The crucial objectives of AI control strategies are to prevent introduction of AI, ease the losses and total eradication of AI. Immune response against the Hemagglutinin (HA) protein and the Neuraminidase (NA) protein by the immune components results in protection against AI. Currently, several conventional and genetically engineered AI vaccines using recombinant technology has been developed and tested in experimental trials. However, its application in commercial chickens has not been studied thoroughly except for conventional and fowlpox virus based vaccines. Vaccination using DNA vaccines is an attractive approach to induce vaccine-induced immunity. On the other hand, DNA vaccine is relatively less immunogenic. Furthermore, several inoculations are required to induce strong vaccine-induced immunity. Different approaches such as adjuvants are available to enhance the immunogenicity of DNA vaccine. The objectives of this study were to construct and express the pcDNA3.1/H5, pcDNA3.1/N1 and pcDNA3.1/NP of H5N1 and to explore the adjuvancy role of Mycobacterial DNA binding Protein-1 (MDP1) in augmenting H5 DNA vaccine in inducing specific antibody response. Constructed pcDNA3.1/MDP1 plasmids encoding MDP1 was obtained from Osaka University, Japan. The complete genes of H5, N1 and NP gene of Malaysian H5N1 virus (A/Ck/Malaysia/5858/04) were cloned separately into pcDNA3.1+ vector. The orientation of the cloned fragments was verified by restriction mapping and DNA sequencing. The expression of protein of the cloned genes was evaluated by transfection of Vero cell lines followed by detection of bands of the expected sized using Western blotting analysis. The immunogenicity of the cloned H5 DNA vaccine was tested in SPF chickens. The chickens were divided into 5 groups namely H5, H5+MDP1, pcDNA3.1, PBS and negative control. The constructed plasmids were injected intramuscularly to 10 days old chickens followed by two booster injections at 14 and 28 days. Bleeding via wing vein was conducted every week post immunization and the collected sera were analyzed using HI test. The HI test showed successful antibody production second week after immunization with an increase in antibody titers during the course of experiment in group inoculated with H5 and H5+MDP1. The result showed that the constructed DNA vaccines were able to induce the production of detectable antibody titer. Furthermore, spleen and muscle samples from chickens inoculated with H5 and H5+MDP1 expressed H5 RNA transcripts. However, the higher antibody titers in chickens inoculated with H5+MDP1 was not statistically significant when compared with chickens inoculated with H5 alone. The highest HI titers for both groups never exceeded 16 HI unit.